Preparation and Characterization of Nickel Ferrite-SiO2/Ag Core/Shell Nanocomposites - I. G. Blanco-Esqueda; G. Ortega-Zarzosa; J. R. Martínez; A. L. Guerrero (Advances in Materials Science and Engineering)
Magnetic composites with silver nanoparticles bonded to their surface were successfully prepared using a simple chemical method. By means of a sol-gel technique, nickel ferrite nanoparticles have been prepared and coated with silica to control and avoid their magnetic agglomeration. The structural and magnetic properties of the nanoparticles were studied in function of the annealing temperature. Then, silver nanoparticles were incorporated by hydrolysis-condensation of tetraethyl orthosilicate, which contains silver nitrate on the surface of the nickel ferrite-SiO2 core/shell. Samples were characterized using X-ray diffraction, IR spectroscopy, SEM, and magnetometry. Results show that the silica covered the nickel ferrite nanoparticles and the silver nanoparticles remain stable in the surface of the composite.